Effect of thermal annealing on the luminescence of defective ZnO nanoparticles synthesized by pulsed laser ablation in water. Issue 10 (7th September 2016) - Camarda, P.; Schneider, R.; Popescu, R.; Vaccaro, L.; Messina, F.; Buscarino, G.; Agnello, S.; Gelardi, F. M.; Cannas, M.
Abstract: This work concerns ZnO nanoparticles (NPs), with sizes of tens of nm, produced by ablation with a pulsed Nd:YAG laser of a Zn plate in H2 O. TEM images evidence the formation of nanoparticles with sizes of tens of nm. Moreover, HRTEM images and Raman spectra show that the distance between the crystalline planes and the vibrational modes are consistent with ZnO nanocrystal in wurtzite structure. Their optical properties are characterized by two emission bands both excited above the energy gap (3.4 eV): the first at 3.3 eV is associated with excitons recombination, the second at 2.2 eV is proposed to originate from a singly ionized oxygen vacancy. The green emission is independent of water pH, thus suggesting that point defects lie inside NPs rather than at the surface. Thermal annealing at 300 °C in O2 and He atmosphere, produces a reduction of the A1 (LO) Raman mode at 562 cm ‐1, which is related to the oxygen vacancies, and a consequent decrease of the defect luminescence, while the excitonic luminescence increases. These results indicate that the ZnO emissions can be controlled by thermal annealing, and are promising in view of optoelectronic applications. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)